PENGARUH PENEMPATAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI SERTA PERAN TUNJANGAN KINERJA SEBAGAI VARIABEL MODERASI (Studi Pegawai di Lingkungan Kecamatan Panggungrejo Kota Pasuruan) - Zainul Arifin; Nasharuddin Mas; Survival (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study uses a quantitative approach with a survey method to test the effect of placement and job characteristics on employee performance, as well as the role of performance allowances as a moderating variable.The population studied was all Civil Servants (PNS) who worked in the Panggungrejo District, Pasuruan City, totaling 124 people. Given the relatively large population in this study, determining the sample size was considered necessary for the efficiency of the research implementation. The sample size in this study was calculated using the Slovin formula, which was 94.66 rounded up to 95 employees. In this study, the sampling technique used was proportional stratified random sampling. This study used Partial Least Square (PLS), which is a Structural Equation Modeling (SEM) equation model. In practice, data processing is assisted by the SmartPLS data processing application.As a result of comprehensive data analysis and structured discussions in the previous chapter, this study concludes several main points as follows: Job placement can play a role in improving employee performance. Job characteristics can play a role in improving employee performance. Although performance allowances are getting stronger, it turns out that they are not able to encourage increased employee performance. Performance allowance plays a role in moderating the influence of job placement on employee performance. Performance allowance plays a role in moderating the influence of job characteristics on employee performance.